Observation research techniques - Urquhart, Christine (Journal of EAHIL, 2016)
This paper outlines the aims of the observation techniques workshop delivered on 11 June 2015, and discusses the experience of the group work sessions. Some participants explained their own experience of observation research, and participants discussed sampling, methods used to collect data and the ethics of observation research. The session participants concluded that observation research was a useful complementary technique for library research. More research published by library and information science practitioners and researchers would help to establish best practice in observation research.